Sejarah, Teori, dan Aplikasi Kritik Sastra Feminis - Cahya Buana (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2009)
Feminist literary criticsm is the therm wich is used to criticize literary works through the examination of female points of view, conserns and values. it encompasses not only female literary works but also male literary works, Generally, feminist literary criticsm to counter, resist and eventually elliminate traditions and conventions of patriarchy ideology of belief system wich sees as